Opioid-preferring participants in drug court: examining participant characteristics and during-program factors associated with program completion. Issue 1 (2nd January 2021) - Shannon, Lisa M.; Jones, Afton Jackson; Newell, Jennifer; Nichols, Elizabeth
ABSTRACT: Drug courts are a community-based rehabilitation program for individuals with substance use and criminal justice system involvement. Building on preliminary research with this Kentucky Specialty Court sample, the study objective was to understand factors associated with drug court completion among opioid-preferring participants. Secondary data, including the participant assessment, Management Information System, and conviction information from a state database, were examined for a sample of opioid-preferring drug court participants (N = 267). Two variables were associated with increased program completion: increasing age and living with partner and children. Four variables were significantly associated with reduced odds of completion: living with partner only, increasing number of pre-drug court felony convictions, receiving a failure-to-appear warrant, and incarceration sanctions/responses. Focused attention on opioid-preferring participants is necessary in order to increase program completion rates and address individualized risks/needs as well as to provide more effective services to such individuals.